Evolutionary and Biomechanical Basis of Drumming Behavior in Woodpeckers - Schuppe, Eric R.; Rutter, Amy R.; Roberts, Thomas J.; Fuxjager, Matthew J. (Frontiers in Ecology and Evolution, 2021)
Understanding how and why behavioral traits diversify during the course of evolution is a longstanding goal of organismal biologists. Historically, this topic is examined from an ecological perspective, where behavioral evolution is thought to occur in response to selection pressures that arise through different social and environmental factors. Yet organismal physiology and biomechanics also play a role in this process by defining the types of behavioral traits that are more or less likely to arise. Our paper explores the interplay between ecological, physiological, and mechanical factors that shape the evolution of an elaborate display in woodpeckers called the drum. Individuals produce this behavior by rapidly hammering their bill on trees in their habitat, and it serves as an aggressive signal during territorial encounters. We describe how different components of the display—namely, speed (bill strikes/beats sec–1), length (total number of beats), and rhythm—differentially evolve likely in response to sexual selection by male-male competition, whereas other components of the display appear more evolutionarily static, possibly due to morphological or physiological constraints. We synthesize research related to principles of avian muscle physiology and ecology to guide inferences about the biomechanical basis of woodpecker drumming. Our aim is to introduce the woodpecker as an ideal study system to study the physiological basis of behavioral evolution and how it relates to selection born through different ecological factors.